Layout optimization in a U-shaped cell using network analysis and the Schmigalla triangular method - Walczak, Maciej (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The workstations layout is important from the point of view of costs and time of production processes. Currently, there are a number of models of placement and methods of its optimization. The U-shaped layout is one of the models used in the design of production cells. This kind of placement became popular with the development of the lean manufacturing concept. The aim of this study is to demonstrate the possibility of optimizing the positioning of the workstations in the U-line using the network programming method and the Schmigalla triangular method.